Effect of hydration with or without n-acetylcysteine on contrast induced nephropathy in patients undergoing coronary angiography and percutaneous coronary intervention (Mymensingh Medical Journal, 2011)
Mymensingh Med J. 2011 Apr;20(2): 264-269 The abstract of this article is available on the PubMed website